2024
DOI: 10.1111/apa.17091
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of socioeconomic factors and COVID‐19 in children and adolescents

Sarah Sahli,
Ketil Størdal

Abstract: AimTo systematically review the evidence on Covid‐19 infection risk, severity and vaccination uptake among children and adolescents by socioeconomic status.MethodsWe conducted a systematic literature review, using the PubMed database. We searched for articles published from January 2020 to January 2022 using “MeSH” words and titles. The key terms were “COVID”, “social status”, “socioeconomic factor” and “children”. We also searched secondary sources such as published reports and other databases.ResultsThe sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Using vaccine uptake as an example, numerous studies have shown that elderly individuals face barriers in accessing vaccination centers despite being a high-risk group [25]. Additionally, socioeconomic factors such as education level and health literacy influence vaccination coverage [26,27]. Certain racial or ethnic groups may also experience disparities in vaccination rates due to mistrust [28][29][30].…”
Section: Applying An Equity Lens To Studying Intervention Harmsmentioning
confidence: 99%
“…Using vaccine uptake as an example, numerous studies have shown that elderly individuals face barriers in accessing vaccination centers despite being a high-risk group [25]. Additionally, socioeconomic factors such as education level and health literacy influence vaccination coverage [26,27]. Certain racial or ethnic groups may also experience disparities in vaccination rates due to mistrust [28][29][30].…”
Section: Applying An Equity Lens To Studying Intervention Harmsmentioning
confidence: 99%